The emergence of chatgpt and its implications for education and academic research in the 21st century - Silva, Altieres de Oliveira; Janes, Diego dos Santos (Review of Artificial Intelligence in Education, 2022)
Objective: The primary objective is to assess how ChatGPT can transform educational practices and academic research, highlighting the opportunities for personalized learning, teaching aid, and research acceleration, as well as the ethical dilemmas and integrity issues it introduces. Method: A qualitative analysis was conducted, reviewing existing literature on ChatGPT's applications in education and research, and synthesizing insights from educators, researchers, and AI experts. The study also incorporates case studies of ChatGPT's deployment in academic settings. Results: Findings suggest that ChatGPT can significantly enhance learning experiences through personalized feedback and support, enrich teaching methodologies, and streamline academic research processes. However, it also raises concerns regarding academic integrity, the authenticity of AI-generated content, and the need for new assessment frameworks. Practical Implications and Conclusions: ChatGPT holds the potential to revolutionize educational and research practices by offering new tools for engagement and efficiency. Nevertheless, to fully leverage its benefits while mitigating risks, it is imperative to establish ethical guidelines, develop sophisticated plagiarism detection tools, and foster a culture of integrity and critical thinking. The study concludes that balancing the innovative capabilities of ChatGPT with a mindful approach to its challenges is crucial for its constructive integration into academic and educational landscapes.